The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1186/1757-7241-22-32
|View full text |Cite
|
Sign up to set email alerts
|

The impact of parental accompaniment in paediatric trauma: a helicopter emergency medical service (HEMS) perspective

Abstract: Major trauma remains a significant cause of mortality and morbidity in young people and adolescents throughout the western world. Both the physical and psychological consequences of trauma are well documented and it is shown that peri-traumatic factors play a large part in the emotional recovery of children involved in trauma. Indeed, parental anxiety levels may play one of the biggest roles. There are no publically available guidelines on pre-hospital accompaniment, and where research has been done on parenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…However, presence during resuscitation in the emergency department has been shown to be psychologically beneficial for family members, particularly if the attempt is unsuccessful, as it decreases post-traumatic stress 23 and facilitates the grieving process 24 . There is very little literature exploring this concept in the prehospital setting, although it has been suggested that parental accompaniment in paediatric trauma requiring helicopter retrieval is probably beneficial for both the patient and the family 25 .…”
Section: Parents and Carersmentioning
confidence: 99%
“…However, presence during resuscitation in the emergency department has been shown to be psychologically beneficial for family members, particularly if the attempt is unsuccessful, as it decreases post-traumatic stress 23 and facilitates the grieving process 24 . There is very little literature exploring this concept in the prehospital setting, although it has been suggested that parental accompaniment in paediatric trauma requiring helicopter retrieval is probably beneficial for both the patient and the family 25 .…”
Section: Parents and Carersmentioning
confidence: 99%
“…19 Family members are impacted too, they may have witnessed the trauma itself, been a first responder, and/or have significant and enduring life-changes as they support their family member's care and recovery. 20 Clearly, early intervention for identifying and addressing psychological and psychosocial impacts of major trauma is an important aspect of care.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to caring for the patient, HEMS personnel have to ensure flight safety, deal with longer transportation times from rural and remote locations, and manage increased noise levels that effectively reduce the crew's ability to communicate. The HEMS factors put additional stress on HEMS personnel (Cowley & Durge, 2014). In addition, the images of patients' conditions and the emergency sites may induce additional traumatic stress (Beck, 2011).…”
Section: Introductionmentioning
confidence: 99%